Factors Associated with Diarrhea Incidence in Toddlers at Datu Beru General Hospital - Saipullah Saipullah (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
Diarrheal diseases remain a global issue with high morbidity and mortality rates in many countries, particularly in developing nations. Indonesia, as one of the developing countries, experiences a high incidence of diarrhea due to its significant morbidity and mortality rates. This study aimed to identify factors associated with the incidence of diarrhea in children under five years old at Datu Beru Regional General Hospital, Central Aceh Regency. The research was an analytical study with a cross-sectional design. The sampling method used was total sampling, involving 64 children under five. Data analysis was conducted using the Chi-Square test and Fisher's Exact test. The study was carried out from May 1 to June 3, 2024. The results revealed a significant relationship between knowledge (P = 0.040), access to information (P = 0.001), and the role of healthcare workers (P = 0.012) and the incidence of diarrhea in children under five. The study concluded that knowledge, access to information, and the role of healthcare workers significantly influence the incidence of diarrhea in children under five. It is recommended to enhance community education on diarrhea prevention, improve access to health information, and optimize the role of healthcare workers through promotive activities such as health education and integrated health services (Posyandu).